Unveiling species diversity in collared frogs through morphological and bioacoustic evidence: a new Mannophryne (Amphibia, Aromobatidae) from Sierra de Aroa, northwestern Venezuela, and an amended definition and call description of M. herminae (Boettger, 1893) - Rojas-Runjaic, Fernando J.m.; Matta-Pereira, Miguel E.; Marca, Enrique La (Zootaxa, 2018)
Species diversity in collared frogs of the genus Mannophryne is presumed to be underestimated due to the paucity of external morphology characters, but combining morphology with bioacoustics and other lines of evidence has shown to be useful in delimiting species of this group. Herein we describe a new species of Mannophryne from Sierra de Aroa in northwestern Venezuela. The new species is morphologically similar to M. herminae but is readily recognized by its strikingly different advertisement call. It also can be distinguished from all its congeners by the unique combination of its small body size, general color pattern, basal toe webbing, and advertisement call consisting of long trills of single tonal notes emitted at a rate of 2–3 notes/s. Additionally, to facilitate future diagnosis of undescribed species related to M. herminae, we amend the definition of the latter, describe in detail its advertisement call, and redefine its known distribution range. The new species increases the number of described species of Mannophryne to 20.